2016
DOI: 10.18805/lr.v0iof.9430
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity analysis in different genotypes of black gram [Vigna mungo (L.) Hepper] using RAPD marker

Abstract: Amongst the various DNA fingerprinting methodologies, randomly amplified polymorphic DNA (RAPD) was used to estimate genetic diversity and relationship amongst 22 black gram genotypes. A total of 25 randomly selected decamers were screened, out of which only 16 got amplified. A total of 133 amplified bands were obtained, out of which 120 were polymorphic. The average percentage of polymorphism was 90.23. The total number of amplified bands varied between 3 (primer OPK-03) and 15 (primer OPC-08) with an average… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
1
3
0
Order By: Relevance
“…Maximum PIC value (0.46) was recorded for UBC 836 among primers. The results of PIC values are conformity with genetic diversity of 22 black gram genotypes by using 15 RAPD primers (Vyas et al, 2016). Similarly the highest PIC value (0.55) Bishoy et al, (2014) reported UBC 887 in genetic diversity study of 17 accessions of Clitoria ternatea using ISSR markers.…”
Section: Results and Discussion Issr Polymorphismsupporting
confidence: 67%
“…Maximum PIC value (0.46) was recorded for UBC 836 among primers. The results of PIC values are conformity with genetic diversity of 22 black gram genotypes by using 15 RAPD primers (Vyas et al, 2016). Similarly the highest PIC value (0.55) Bishoy et al, (2014) reported UBC 887 in genetic diversity study of 17 accessions of Clitoria ternatea using ISSR markers.…”
Section: Results and Discussion Issr Polymorphismsupporting
confidence: 67%
“…Four loci of 400, 600, 1,100 and 2,200 bp in length are observed. Extremely distinct result with OPP-08 showing a 100% polymorphism in black gram (Vigna mungo) was reported (Vyas et al, 2016). In addition, OPP-08 resulted in 91.7% polymorphism in fenugreek (Trigonella foenum-graecum) (Tomar et al, 2014).…”
Section: Resultsmentioning
confidence: 97%
“…These primers were synthesized by Sigma-Aldrich and the sequences were used in previous studies on disease resistance in black gram (Basak et al 2004; Vyas et al 2016). Of the 40, only 33 RAPD primers produced clear and reproducible banding patterns.…”
Section: Methodsmentioning
confidence: 99%
“…However, high genetic consistency and the absence of suitable ideotypes reinforce with deficient harvest and disease susceptibility has caused major constraints in achieving a higher yield (Vyas et al 2016). Among various biotic factors affecting black gram yield, the main diseases which devastate the crops are mung bean yellow mosaic virus (MYMV), urdbean leaf crinkle virus (UCLV), powdery mildew (PM) and wilt ( Fusarium oxysporum ).…”
Section: Introductionmentioning
confidence: 99%